Mitigating Cognitive Bias to Improve Organizational Decisions: An Integrative Review, Framework, and Research Agenda - Fasolo, Barbara; Heard, Claire; Scopelliti, Irene (Journal of Management, 2025)
The detrimental influence of cognitive biases on decision-making and organizational performance is well established in management research. However, less attention has been given to bias mitigation interventions for improving organizational decisions. Drawing from the judgment and decision-making (JDM) literature, this paper offers a clear conceptualization of two approaches that mitigate bias via distinct cognitive mechanisms—debiasing and choice architecture—and presents a comprehensive integrative review of interventions tested experimentally within each approach. Observing a lack of comparative studies, we propose a novel framework that lays the foundation for future empirical research in bias mitigation. This framework identifies decision, organizational, and individual-level factors that are proposed to moderate the effectiveness of bias mitigation approaches across different contexts and can guide organizations in selecting the most suitable approach. By bridging JDM and management research, we offer a comprehensive research agenda and guidelines to select the most suitable evidence-based approach for improving decision-making processes and, ultimately, organizational performance.